2014
DOI: 10.1021/cs501573c
|View full text |Cite
|
Sign up to set email alerts
|

Double-Supported Silica-Metal–Organic Framework Palladium Nanocatalyst for the Aerobic Oxidation of Alcohols under Batch and Continuous Flow Regimes

Abstract: This is the accepted version of a paper published in ACS Catalysis. This paper has been peerreviewed but does not include the final publisher proof-corrections or journal pagination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 52 publications
1
48
0
Order By: Relevance
“…Interestingly, the XRPD pattern of the recovered material revealed that the framework did not decompose after five reaction runs (Figure a), despite the previously reported detrimental effect of carbonates on its mesoporous polymorph MIL‐101‐NH 2 . Slight changes were observed in the 2Θ value and relative intensities of the main diffraction peaks; this has been reported previously for this MOF, and ascribed to its flexible nature . On the other hand, the activity of the catalyst was retained only until the second run, when a yield of 70 % of the main product was obtained (Figure b, blue bars).…”
Section: Resultssupporting
confidence: 51%
See 2 more Smart Citations
“…Interestingly, the XRPD pattern of the recovered material revealed that the framework did not decompose after five reaction runs (Figure a), despite the previously reported detrimental effect of carbonates on its mesoporous polymorph MIL‐101‐NH 2 . Slight changes were observed in the 2Θ value and relative intensities of the main diffraction peaks; this has been reported previously for this MOF, and ascribed to its flexible nature . On the other hand, the activity of the catalyst was retained only until the second run, when a yield of 70 % of the main product was obtained (Figure b, blue bars).…”
Section: Resultssupporting
confidence: 51%
“…Our group has developed several procedures using Pd nanoparticles supported on MIL‐101‐NH 2 (Cr) and MIL‐88B‐NH 2 (Cr). The excellent catalytic activity of the resulting materials has been demonstrated in a wide variety of transformations, including Suzuki‐Miyaura cross‐couplings, C−H activation/halogenations, selective C=C hydrogenations, Heck couplings, different carbonylation reactions and the aerobic oxidation of benzylic alcohols . The catalytic methods we developed using these heterogeneous Pd catalysts were efficient, and in some cases they even surpassed their homogeneous counterparts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our group has gained extensive experience in the development of heterogeneous processes catalyzed by MOF‐supported Pd nanoparticles. Excellent activity together with an important contribution from the solid support were observed in reactions such as C−C cross‐couplings, alcohol oxidation, C−H functionalization, and selective C=C hydrogenation . However, in some cases significant structural differences were observed between the fresh and recycled catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Representation of the synthesis of Pd@MIL-88B-NH 2 @nano-SiO 2 .TEOS = tetraethyl orthosilicate.R eprinted with permission from Ref. [47].Copyright 2015A merican Chemical Society. Figure 6.…”
Section: Redox Reactionsmentioning
confidence: 99%